Impact of technology on structural change of labor in the manufacturing and processing industry of Vietnam - Vu, Thanh Huong; Ha, Dieu Linh; Le, Phuong Thao (Journal of Social Economics Research, 2023)
This study examines the effects of technological advancements on changes in the labor structure within Vietnam’s manufacturing and processing industries. The study utilizes a panel dataset that combines each year’s enterprise census data from 2012 to 2018 with the enterprise statistics of technology data provided by the Vietnam General Statistics Office throughout the same timeframe. This study highlighted four key aspects that contribute to technology-related challenges. These factors include external technology purchasing, research and development activities, absorbability of technology, and the influence of Foreign Direct Investment firms. The study tested the endogeneity in the model, overcame the defects of the model, and selected the fixed effect model to assess the four factors affecting labor structural change. The Lilien index is used to measure the level of structural change in labor in the manufacturing and processing industries of Vietnam. The results show that external technology acquisition and R&D activities had a positive effect on the Lilien index. Moreover, compelling data indicates that the location of technology acquisition has a contrasting influence on labour structural change, with varying effects observed in enterprises that employ high versus low levels of technology. The findings will serve as a significant indicator for governmental entities and management in formulating policies aimed at enhancing the overall efficiency of firms and facilitating labour restructuring initiatives.